Motivasi Belajar Siswa SMA pada Pembelajaran Daring di Masa Pandemi Covid-19 - Cahyani, Adhetya; Listiana, Iin Diah; Larasati, Sari Puteri Deta (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
Education system in Indonesia is experiencing new challenges due to the Covid-19 virusoutbreak, which has caused the entire learning system in educational institutions to betransferred to online learning methods. The disruption in the learning process causes somechanges to students which ultimately affect the motivation to learn. This research uses aquantitative approach, with the sampling technique used is accidental sampling. The populationin this study were all high school students who took part in the process online learning. Theanalytical method used to analyze the data obtained in this study uses the Mann Whitney Uanalysis method. This type of research uses the foundation of learning motivation theory andaspects from Chernis & Goleman's theory (2011). The results of this study indicate that thesignificance value of Mann Whitney U is 0,000 which means the motivation to learn in students who take online or online learning in the midst of the pandemic situation of the Covid-19 virusis decreasing, because the significance value of 0,000 is less than 0.05 (p <0,05).